Regression of genital papules and mild cervical intraepithelial neoplasia during immunotherapy (clinical case) - S.I. Rogovskaya; Bebneva T.N (LCC «Medicine-Inform», 2020)
S.I. Rogovskaya1, T.N. Bebneva2,3 1Public organization «RAGIN», Moscow, Russian Federation 2Peoples' Friendship University of Russia, Moscow, Russian Federation 3National Medical Research Center of Endocrinology, Moscow, Russian Federation The article is devoted to one of the most urgent problems in cervicology - diseases associated with the human papillomavirus (HPV). It is known that one of the co-risk factors for HPV persistence is a decrease in local immunity (deficiency of macrophages). The problem of cervical intraepithelial neoplasia (CIN) management is actualized by the tendency to increase this disease incidence; as a rule, the treatment of such patients consists in removing the infected tissue. Given that even after complete removal of HPV-infected tissues, CIN relapse may occur; national and foreign scientific literature increasingly focuses on auxiliary immunotherapy not only as prevention of relapses but also to stimulate the body's defences. This publication uses a clinical example to consider patient management with a clinical form of HPV infection (genital papules) and a subclinical form (mild intraepithelial lesion). Immunotherapy use in the treatment of patients with HPV-asso ciated diseases increases the efficacy of the main therapy and leads to HPV elimination. Keywords: human papillomavirus, neoplasia, papules, LSIL, phagocyte, immunomodulator, COX-2, Polyoxidonium. For citation: Rogovskaya S.I., Bebneva T.N. Regression of genital papules and mild cervical intraepithelial neoplasia during immunotherapy (clinical case). Russian Journal of Woman and Child Health. 2020;3(2):100-104. DOI: 10.32364/2618-8430-2020-3-2-100-104.